Isolation of Pathogenic Bacteria from Inanimate Surfaces and contaminated Equipments in Intensive Care Unit at Zawia Teaching Hospital, Libya - Salma Alamari; Gada Algeblaue (AlQalam Journal of Medical and Applied Sciences, 2020)
Bacterial infections are responsible for great number of mortalities in the Intensive Care Units (ICUs). ICU-acquired infections are a challenging health problem worldwide, especially when caused by multidrug-resistant (MDR) pathogens. Cross-transmission of microorganisms from inanimate surfaces may have a significant role in ICU-acquired colonization and infections. This study aimed at isolating and identifying the pathogenic bacteria from equipment surface in the intensive care unit at Zawia teaching hospital, and to evaluate the impact of sterilization and disinfectants on the equipment used in these ICUs. METHODS: The study was carried in the period from April to May 2018. A total of 56 frequently used equipments and devices in ICUs were sampled by using a sterile swab moistened with Trypticase Soy Broth (TSB) medium, according to standard bacteriological procedures. Data were presented as counts and percentage using Excel spread data sheath. RESULTS: Out of 56 samples, 7(12.5%) shows no bacterial growth, 23(41.1%) samples exhibited the presence of pathogenic bacteria (Escherichia coli, Serratia marcescens, Staphylococcus hemolytic, Pseudomonas aeruginosa, Acinetobacter baumanii, Klebsiella pneumonia, Coagulase negative Staphylococci, Serratia marcescens), and 26(46.4%) samples contaminated with non-pathogenic Diphtheria and coagulase-negative staphylococci and mixed flora. CONCLUSION: There were no sterilization and disinfection in ICU at Zawia Teaching hospital, and the pathogenic bacteria everywhere.